The Impact of Moderate-Dose Acetylsalicylic Acid in the Reduction of Inflammatory Cytokine and Prevention of Complication in Acute Phase of Kawasaki Disease: The Benefit of Moderate-Dose Acetylsalicylic Acid - Jung Eun Kwon; Da Eun Roh; Yeo Hyang Kim (Children, 2020)
Background: Acetylsalicylic acid (ASA) is part of the recommended treatment of Kawasaki disease (KD). Controversies remain regarding the optimal dose of ASA. We aimed to evaluate the impact of different doses of ASA on inflammation control while minimizing adverse effects in the acute phase treatment of KD. Methods: The enrolled 323 patients with KD were divided into three groups according to ASA dose: moderate-dose (30–50 mg/kg/day), high-dose (80–100 mg/kg/day), and non-ASA. Results: High-dose ASA group showed a significantly shorter duration of fever from the start of treatment to remission than other groups. Baseline level and delta score of interleukin (IL)-1, IL-6, IL-10, tumor necrosis factor-α, and transforming growth factor β were not statistically different among the groups. The number of patients who received additional treatments in the non-ASA group was more than other groups. Coronary artery dilatation was not significantly different among the groups. One patient with high-dose ASA was diagnosed with Reye syndrome. Conclusion: Different doses of ASA did not show any differences in changes of inflammatory bio-makers and cytokines. However, high-dose ASA showed occurrence of Reye syndrome, and non-ASA showed intravenous immunoglobulin refractoriness. We suggest that moderate-dose ASA may be beneficial for the treatment of patients in the acute phase of KD.